2013
DOI: 10.1111/joor.12107
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of wearing complete dentures on bolus transport during feeding in elderly edentulous

Abstract: Prosthetic treatment with dentures is often required for the elderly who have reduced swallowing function. Therefore, it is important to understand the relationship between denture-wearing and feeding function from the perspective of swallowing. To clarify changes in bolus transport during feeding in elderly edentulous patients with or without complete dentures. Subjects were 15 elderly edentulous volunteers who were treated with maxillary and mandibular complete dentures. The test food was 10 g of minced agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 25 publications
4
45
0
2
Order By: Relevance
“…In the other studies, the consistencies and volumes varied among them, as there was no standardization and therefore difficult to perform analysis between the consistency and the location of the onset of the pharyngeal phase of swallowing. With regard to onset of the pharyngeal phase, 50% (six articles) reported discharge in the vallecula (2,(6)(7)(8)17,19) ; 25% (three articles) above, at or below the mandibular ramus (12,16,20) ; 16% (two articles) to dorsum of the tongue (2,6) ; 16% (two articles) to hypopharynx (8,21) ; 16% (two articles) to oropharynx (21,22) ; 8% (one article) to tongue (6) ; 8% (one article) to pyriform sinus (18) and 8% (one article) to oral cavity (7) . In some studies, the onset location of the pharyngeal phase was observed in more than one region for the same individuals (2,(6)(7)(8)21) .…”
Section: Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In the other studies, the consistencies and volumes varied among them, as there was no standardization and therefore difficult to perform analysis between the consistency and the location of the onset of the pharyngeal phase of swallowing. With regard to onset of the pharyngeal phase, 50% (six articles) reported discharge in the vallecula (2,(6)(7)(8)17,19) ; 25% (three articles) above, at or below the mandibular ramus (12,16,20) ; 16% (two articles) to dorsum of the tongue (2,6) ; 16% (two articles) to hypopharynx (8,21) ; 16% (two articles) to oropharynx (21,22) ; 8% (one article) to tongue (6) ; 8% (one article) to pyriform sinus (18) and 8% (one article) to oral cavity (7) . In some studies, the onset location of the pharyngeal phase was observed in more than one region for the same individuals (2,(6)(7)(8)21) .…”
Section: Overviewmentioning
confidence: 99%
“…With regard to onset of the pharyngeal phase, 50% (six articles) reported discharge in the vallecula (2,(6)(7)(8)17,19) ; 25% (three articles) above, at or below the mandibular ramus (12,16,20) ; 16% (two articles) to dorsum of the tongue (2,6) ; 16% (two articles) to hypopharynx (8,21) ; 16% (two articles) to oropharynx (21,22) ; 8% (one article) to tongue (6) ; 8% (one article) to pyriform sinus (18) and 8% (one article) to oral cavity (7) . In some studies, the onset location of the pharyngeal phase was observed in more than one region for the same individuals (2,(6)(7)(8)21) . More than one location was also observed for pharyngeal phase onset in eight studies (2,(6)(7)(8)12,16,20,21) , thus, some items were repeated in the calculation of the above percentages.…”
Section: Overviewmentioning
confidence: 99%
See 3 more Smart Citations